Narrative in the feminine : Daphne Marlatt and Nicole Brossard - Knutson, Susan Lynne (Waterloo, Ont. : Wilfrid Laurier University Press, 2000)
What does it mean to tell a story from a woman's point of view? How have Canadian Anglo/francophone writers translated feminist literary theory into practice? These and other questions are answered by these two avant-garde authors. It is also a study of two of their own important works.
Gender and narrative grammar -- A narratological reading of How Hug a Stone -- A narratological reading Picture Theory -- Afterword.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Marlatt, Daphne; Brossard, Nicole; Marlatt, Daphne, -- 1942-; Brossard, Nicole, -- 1943-; Brossard, Nicole; Marlatt, Daphne; Feminist literary criticism; Dialogue in literature; Canadian literature -- Women authors -- History and criticism; Canadian literature -- 20th century -- History and criticism; Feminist criticism; Critique féministe.; Dialogue dans la littérature.; Écrits de femmes canadiens -- Histoire et critique; Littérature canadienne -- 20e siècle -- Histoire et critique; POETRY -- American -- General; Feminist criticism; Canadian literature; Canadian literature -- Women authors; Dialogue in literature; Feminist literary criticism; Feminismus; Frauenliteratur; Kanada; 1900-1999; Electronic books; Criticism, interpretation, etc